Effect of Training Variations on Tennis Groundstroke Forehand Ability for Beginner Tennis - Mario Febrian; Andre Igoresky; Indri Wulandari; Diah Fauzi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2026)
Forehand is the most basic and easiest stroke to teach in tennis. This study investigated the effect of variations in forehand training on the forehand groundstroke ability of beginner tennis athletes in padang. The sample was taken from beginner tennis athletes in padang, grouped according to their forehand groundstroke ability. Each group received forehand groundstroke training with different variations: fixed position and shifting position The results showed a significant effect of variations in forehand groundstroke training on forehand groundstroke ability in tennis. This was demonstrated by the t-test results, where t-test (9.237) > t-table (2.457). The t-test results revealed an effect of variations in forehand groundstroke training on the initial ability of beginner tennis athletes in padang. However, the study found that variations in forehand groundstroke training with fixed position were more effective than variations in shifting position on forehand groundstroke ability in tennis for beginner tennis athletes in padang.